Functional non-parametric mixed effects models for cytotoxicity assessment and clustering - Ma, Tiantian; Richard, Dan; Yang, Yongqing Betty; Kashlak, Adam B.; Anton, Cristina (My University, 2023)
A multitude of natural and synthetic chemicals are present in our environment. Through the study of a compound’s cytotoxicity, researchers can carefully set regulations regarding how much of a certain chemical in the ambient environment is tolerable. In the past, research has focused on point measurements such as the LD50. Instead, we consider entire time-dependent cellular response curves through the application of functional mixed effects models. We identify differences in such curves corresponding to the chemical’s mode of action—i.e. how the compound attacks human cells. Through such analysis, we identify curve features to be used for cluster analysis via application of both k-means and self organizing maps. The data is analyzed by making use of functional principal components as a data driven basis and separately by considering B-splines for identifying local-time features. Our analysis can be used to drastically speed up future cytotoxicity research.
Keywords: cytotoxicity; time-dependent cellular response curves